Resident-Guided Case Discussions in Reproductive Endocrinology & Infertility - Brenda Houmard; Leslie McLemore; Seine Chiang (Association of American Medical Colleges, 2012)
Abstract This resource is a series of resident-guided case discussions in reproductive endocrinology and infertility. It is designed to be an adjunctive curriculum tool to allow trainees in gynecology to improve their comfort with core concepts in reproductive endocrinology and infertility. The sequential cases in this resource include attached questions and reading lists. Clinical experience in reproductive endocrinology and infertility is variable among trainees. Structured case-based learning allows gynecology trainees to be exposed to a core of common concepts in reproductive endocrinology. This exercise provides opportunities for medical trainees to explore ACGME competencies in clinical cases outside of the clinical arena. In addition, it allows senior instructors (such as residents and fellows) the opportunity to formally gain educational skills by teaching clinical concepts in a supervised environment while enhancing their own knowledge of reproductive endocrinology and infertility concepts. The team completing these cases consists of a learner, a teacher, and a faculty mentor. Each case is presented and discussed in 30 minutes. The clinical scenarios are presented in a fashion that mimics clinical dilemmas. The trainees explore the diagnosis, evaluation, management, and other treatment options. A reading list is provided with three or four segments of clinical questioning. Evaluations of teaching/learning skills, as well as ACGME competencies, are attached and completed for both learner and teacher trainees. Feedback from junior and senior gynecology resident trainees has consistently indicated that this is a worthwhile program as it allows for the curriculum to be standardized among the residents and for learning to occur outside of the clinical arena.